Ecological Crisis as a Catalyst for Moral Transformation in The Lion King and WALL-E: An Ecocritical Comparative Study - Monica Margaretha; Rahayu Puji Haryanti (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study examines the representation of ecological crises and the moral transformation of leader characters in The Lion King (1994) and WALL-E (2008). It aims to identify forms of ecological crises depicted in both films, analyze their role in shaping leaders’ moral development, and compare their similarities and differences. Using a qualitative descriptive method with an ecocritical approach, the study analyzes dialogues, scenes, and visual elements based on Greg Garrard’s ecocritical concepts, including animals, wilderness, pollution, apocalypse, and dwelling. The findings show that The Lion King represents ecological crises through habitat destruction, ecosystem imbalance, and environmental degradation, reflecting animals and wilderness. In contrast, WALL-E portrays ecological crises through excessive waste, pollution, and an uninhabitable Earth, reflecting pollution and apocalypse. In both films, ecological crises act as catalysts for leaders’ moral transformation. Simba becomes a responsible leader restoring ecological balance, while Captain develops environmental awareness and responsibility for Earth’s recovery. Although both films highlight environmental threats, they differ in problem focus and recovery strategies. The study concludes that both films emphasize leadership, responsibility, and ecological balance in sustaining life.